Accidental Left Circumflex Artery to Right Lung Fistula in a Suspected Case of Pulmonary Hypertension - Saeed Alipourparsa; Isa Khaheshi; Vahid Eslami; Mohammadreza Bozorgmanesh; Habib Haybar (Case Reports in Cardiology)
A 56-year-old woman was referred to the cardiology department of the Shahid Modarres hospital. The patient had a history of pulmonary thromboembolism 20 years ago which had been managed by the inferior vena cava filter and since then the patient has been on warfarin. Her chief complaint was chronic dyspnea on exertion (NYHA class II) from several years ago. Right and left heart catheterization was performed for evaluation of pulmonary artery pressure. We found rich collateral formations between LCX as well as RCA and right pulmonary artery, primarily assumed as multiple fistulas. Among patients who have chronic thromboembolic pulmonary hypertension, systemic collateral supply to the pulmonary parenchyma has been previously reported to occur from both bronchial and/or nonbronchial systemic circulations. Our patient had neither signs of heart failure nor myocardial ischemia and, thus, was a candidate for conservative management. The adenosine pulmonary reactivity test was not performed because of low pulmonary pressure which had been estimated to be high.